Master of Education research portfolio - Iitula, Helena (Rhodes University, Faculty of Education, Department of Education, 2006)
This Portfolio was submitted in 2005 to Rhodes University as a Research Portfolio presented in partial fulfilment of the requirements for the degree of Master of Education in General Education Theory and Practice. The Portfolio consists of seven (7) key parts. The reader of this Portfolio is courteously informed that the structure of this portfolio is to some extent differ from the thesis structure. Thus, the reader should be attentive not to weigh against the two. Further more, I hereby declare that this portfolio is my own work and that all the sources that I have used or quoted have been indicated and acknowledged by means of references indicated at the end of each part. Part 2 and 6 are the core parts of the portfolio. The focal point of part 2 is the contextual curriculum analysis of Grade 8-10 Oshindonga Curriculum in order to investigate its implementation in four educational circuits: Oshigambo, Onathinge, Onyaanya and Omuthiya in Oshikoto Region. Based on the findings of this analysis, lack of critical inquiry and reflective practice among Oshindonga teachers was identified as one of the major obstacles that preventing the effective implementation of the curriculum. Most of these teachers are Basic Education Teacher Diploma (BETD) postgraduates. Thus, part 3 and 4 were developed as supplements to inform the main research paper (part 6) which is related to teacher's professionalism in the classroom. The focus of part 3 (literature review) was on the teacher as a reflective practitioner. This is in line with the Namibian Education Policy, which identifies reflective practice as the heart of teacher professionalism. In this part, I explored a variety of views related to the notion of professionalism in teaching. I have also focused on views related to teacher's professional development both on macro and micro levels. These views provided a clarification and an underpinning framework on which to base my analysis of reflective practice as professionalism in education. Part 4 (education theories) focused on the digging of understanding of knowledge as an important theoretical domain of behaviourist and constructivist theories. I have tried to establish how the two theories (Behaviourist and Constructivist) view knowledge and its acquisition and to gain an understanding of how the two theories have been informing the practice. Subsequently, part 6 meant to investigate and assess the extent to which Basic Education Teacher Diploma postgraduate teachers are autonomously applying the theory of critical inquiry and reflective practice in the classroom. Both part 2 and 6 have findings. There is much correlation between the issues and problems in the implementation of the curriculum as identified in part 2 and the findings of the main research paper (part 6). Though critical inquiry and reflective practice is the key journey towards a high level of reflectivity and one of the significant characters of teacher professionalism in the classroom, most issues and problems identified were related to the insufficient practice of critical inquiry and reflective practices. Low correlation was found between critical inquiry and reflective practice theory and teachers' practices in the classroom. Despite to the fact that various rationales were mentioned as to why critical inquiry and reflective practice successful implementation is not taking place, the study positioned an emphasis on team working at school, cluster and circuit base that could contributed to a great extend to making teachers more competent and supporting themselves in mastering the applicable critical inquiry and reflective practice skills.
Keywords: Education -- Namibia; Curriculum planning -- Namibia; Education and state -- Namibia; Competency-based education -- Namibia; Teachers -- Training of -- Namibia; Education, Secondary -- Namibia